Casein Kinase 1 Regulates Cytorhabdovirus Replication and Transcription by Phosphorylating a Phosphoprotein Serine-Rich Motif. Issue 9 (8th July 2020) - Gao, Qiang; Yan, Teng; Zhang, Zhen-Jia; Liu, Song-Yu; Fang, Xiao-Dong; Gao, Dong-Min; Yang, Yi-Zhou; Xu, Wen-Ya; Qiao, Ji-Hui; Cao, Qing; Ding, Zhi-Hang; Wang, Ying; et al.
Abstract : Casein kinase 1 regulates cross-kingdom infections of a cytorhabdovirus in host plants and insect vectors by phosphorylating an intrinsically disordered region of viral phosphoprotein. Abstract: Casein kinase 1 (CK1) family members are conserved Ser/Thr protein kinases that regulate important developmental processes in all eukaryotic organisms. However, the functions of CK1 in plant immunity remain largely unknown. Barley yellow striate mosaic virus (BYSMV), a plant cytorhabdovirus, infects cereal crops and is obligately transmitted by the small brown planthopper (SBPH; Laodelphax striatellus ). The BYSMV phosphoprotein (P) exists as two forms with different mobilities corresponding to 42 kD (P42) and 44 kD (P44) in SDS-PAGE gels. Mass spectrometric analyses revealed a highly phosphorylated serine-rich (SR) motif at the C-terminal intrinsically disordered region of the P protein. The Ala-substitution mutant (P S5A ) in the SR motif stimulated virus replication, whereas the phosphorylation-mimic mutant (P S5D ) facilitated virus transcription. Furthermore, P S5A and P S5D associated preferentially with nucleocapsid protein–RNA templates and the large polymerase protein to provide optimal replication and transcription complexes, respectively. Biochemistry assays demonstrated that plant and insect CK1 protein kinases could phosphorylate the SR motif and induce conformational changes from P42 to P44. Moreover, overexpression of CK1 or a dominant-negative mutant impaired the balance between P42 and P44, thereby compromising virus infections. Our results demonstrate that BYSMV recruits the conserved CK1 kinases to achieve its cross-kingdom infection in host plants and insect vectors.